The Urgency of Imprisonment as a Substitute for Restitution in Upholding Justice for Rape Victims - Khoirudin Khoirudin; Hono Sejati; Mohamad Tohari (Dinasti Research, 2024)
The legal vacuum regarding imprisonment as a substitute for restitution in Indonesia is a serious issue that directly affects the enforcement of justice for rape victims. In many cases, perpetrators of crimes are often unable to pay the restitution that should be afforded to victims, thereby denying victims their rights to receive compensation for the harm suffered. This legal uncertainty not only hampers the psychological and emotional recovery of victims but also creates a perception that the justice system is unable to deliver the justice it should. This article examines the urgency of implementing imprisonment as a substitute sanction for perpetrators who are unable to pay restitution, as well as exploring the weaknesses in existing legislation and efforts that can be made to address this legal vacuum. Through appropriate legal reforms, it is hoped that the rights of victims can be effectively protected, and the criminal justice system can impose appropriate sanctions on perpetrators, thereby enhancing public trust in justice.